2017
DOI: 10.1074/mcp.ra117.000015
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Proteins in Dried Blood Spot Biobanks

Abstract: An important motivation for the construction of biobanks is to discover biomarkers that identify diseases at early, potentially curable stages. This will require biobanks from large numbers of individuals, preferably sampled repeatedly, where the samples are collected and stored under conditions that preserve potential biomarkers. Dried blood samples are attractive for biobanking because of the ease and low cost of collection and storage. Here we have investigated their suitability for protein measurements. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 34 publications
(43 reference statements)
2
72
0
1
Order By: Relevance
“…In Ontario, Canada, samples are stored for 19 years before they are destroyed 13 . Protein, DNA and other potential targets from dried blood spots have been shown to be stable over many years 14 17 . However, the stability of individual analytes used to interpret newborn screening profiles after exposure to different storage conditions has been found to be largely variable.…”
Section: Discussionmentioning
confidence: 99%
“…In Ontario, Canada, samples are stored for 19 years before they are destroyed 13 . Protein, DNA and other potential targets from dried blood spots have been shown to be stable over many years 14 17 . However, the stability of individual analytes used to interpret newborn screening profiles after exposure to different storage conditions has been found to be largely variable.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of dried blood spots are of particular interest for comparative metabolomics studies conducted in remote locations, and those having large cohorts from multiple collaborating centers [9]. In recent years, due to the above benefits, DBS have also been increasingly used in various other fields, such as therapeutic drug and abused substances monitoring [8,10], pharmacokinetics [11], proteomics [12], lipidomics [13,14], and metabolomics [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…2). We furthermore found that the levels of most proteins remained stable upon storage for tens of years [41]. For those proteins whose levels showed a tendency to slowly decrease over time, storage at −24°C better preserved levels than did +4°C This means that very large biobanks can be built at little cost by simply drying drops of blood on paper and preserving these cold.…”
Section: What Samples Should Be Collected For Analysis Of Protein Marmentioning
confidence: 99%